Time and cost of linking administrative datasets for outcomes assessment in a follow-up study of participants from two randomised trials - Mohammad Shahbaz; Jane E. Harding; Barry Milne; Anthony Walters; Lisa Underwood; Martin von Randow; Lena Jacob; Greg D. Gamble; for the ANCHOR Study Group (BMC Medical Research Methodology)
Abstract Background For the follow-up of participants in randomised trials, data linkage is thought a more cost-efficient method for assessing outcomes. However, researchers often encounter technical and budgetary challenges. Data requests often require a significant amount of information from researchers, and can take several years to process. This study aimed to determine the feasibility, direct costs and the total time required to access administrative datasets for assessment of outcomes in a follow-up study of two randomised trials. Methods We applied to access administrative datasets from New Zealand government agencies. All actions of study team members, along with their corresponding dates, were recorded prospectively for accessing data from each agency. Team members estimated the average time they spent on each action, and invoices from agencies were recorded. Additionally, we compared the estimated costs and time required for data linkage with those for obtaining self-reported questionnaires and conducting in-person assessments. Results Eight agencies were approached to supply data, of which seven gave approval. The time from first enquiry to receiving an initial dataset ranged from 96 to 854 days. For 859 participants, the estimated time required to obtain outcome data from agencies was 1,530 min; to obtain completed self-reported questionnaires was 11,025 min; and to complete in-person assessments was 77,310 min. The estimated total costs were 20,827 NZD for data linkage, 11,735 NZD for self-reported questionnaires, and 116,085 NZD for in-person assessments. Using this data, we estimate that for a cohort of 100 participants, the costs would be similar for data linkage and in-person assessments. For a cohort of 5,000 participants, we estimate that costs would be similar for data linkage and questionnaires, but ten-fold higher for in-person assessments. Conclusions Obtaining administrative datasets demands a substantial amount of time and effort. However, data linkage is a feasible method for outcome ascertainment in follow-up studies in New Zealand. For large cohorts, data linkage is likely to be less costly, whereas for small cohorts, in-person assessment has similar costs but is likely to be faster and allows direct assessment of outcomes.